2020
DOI: 10.22437/jssh.v4i1.9921
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas Dan Likuiditas Terhadap NILAI Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar Di BEI Periode 2007-2018

Abstract: Nilai perusahaan merupakan tolak ukur keberhasilan manajemen perusahaan dalam mengelola operasional perusahaan sehingga meningkatkan kepercayaan pemegang saham. Penelitian ini bertujuan untuk menganalisis pengaruh ukuran perusahaan, leverage, profitabilitas dan likuiditas sebagai faktor yang mempengaruhi nilai perusahaan pada perusahaan Sektor Industi Barang Konsumsi yang terdaftar di Bursa Efek Indonesia periode 2007-2018. Penelitian ini juga akan menguji variabel kebijakan dividen yang dijadikan sebagai vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 8 publications
1
7
1
5
Order By: Relevance
“…The results of this study are in line with research conducted by Husna and Satria [10] which states that the size of the company negatively affects the value of the company. This study contradicts research conducted by Husna and Satria [10], and Aldi, et al [11], which showed that the size of the company had a significant positive effect on the company's value.…”
Section: F Effect Of Company Size On Company Valuecontrasting
confidence: 88%
“…The results of this study are in line with research conducted by Husna and Satria [10] which states that the size of the company negatively affects the value of the company. This study contradicts research conducted by Husna and Satria [10], and Aldi, et al [11], which showed that the size of the company had a significant positive effect on the company's value.…”
Section: F Effect Of Company Size On Company Valuecontrasting
confidence: 88%
“…With managerial ownership in a company, it is expected that company managers can be more careful with this liquidity ratio, because the decisions that will be taken by management will affect the shares held by managers. Meanwhile, based on previous research, it shows that managerial ownership is able to moderate the relationship between liquidity and firm valu e (Aldi et al, 2020). Based on the explanation above, the first hypothesis derived is: H 6 .…”
Section: Liquidity and Firm Value With Managerial Ownership As Modera...mentioning
confidence: 95%
“…Harga saham adalah "Harga suatu saham yang terjadi pasar bursa pada saat tertentu yang ditentukan oleh pelaku pasar dan ditentukan oleh permintaan dan penawaran saham yang bersangkutan di pasar modal" (Vianastie, et al, 2022). Harga saham merupakan harga yang dibentuk dari interaksi para penjual dan pembeli saham yang dilatarbelakangi oleh harapan terhadap profit perusahaan (Aldi, et al, 2020).…”
Section: Harga Sahamunclassified